Tungsten(VI) Carbyne/Bis(carbene) Tautomerization Enabled by N‐Donor SBA15 Surface Ligands: A Solid‐State NMR and DFT Study. Issue 37 (11th August 2016) - Bendjeriou‐Sedjerari, Anissa; Sofack‐Kreutzer, Julien; Minenkov, Yury; Abou‐Hamad, Edy; Hamzaoui, Bilel; Werghi, Baraa; Anjum, Dalaver H.; Cavallo, Luigi; Huang, Kuo‐Wei; Basset, Jean‐Marie
Abstract: Designing supported well‐defined bis(carbene) complexes remains a key challenge in heterogeneous catalysis. The reaction of W(≡C t Bu)(CH2 t Bu)3 with amine‐modified mesoporous SBA15 silica, which has vicinal silanol/silylamine pairs [(≡SiOH)(≡SiNH2 )], leads to [(≡SiNH2 −)(≡SiO−)W(≡CH t Bu)(CH2 t Bu)2 ] and [(≡SiNH2 −)(≡SiO−)W(=CH t Bu)2 (CH2 t Bu). Variable temperature, 1 H– 1 H 2D double‐quantum, 1 H– 13 C HETCOR, and HETCOR with spin diffusion solid‐state NMR spectroscopy demonstrate tautomerization between the alkyl alkylidyne and the bis(alkylidene) on the SBA15 surface. Such equilibrium is possible through the coordination of W to the surface [(≡Si−OH)(≡Si−NH2 )] groups, which act as a [N, O] pincer ligand. DFT calculations provide a rationalization for the surface–complex tautomerization and support the experimental results. This direct observation of such a process shows the strong similarity between molecular mechanisms in homogeneous and heterogeneous catalysis. In propane metathesis (at 150 °C), the tungsten bis(carbene) tautomer is favorable, with a turnover number (TON) of 262. It is the highest TON among all the tungsten alkyl‐supported catalysts. Abstract : O brave HETCOR! Look how it binds ! Solid‐state NMR was used to demonstrate the tautomerization of the alkyl alkylidyne and bis(alkylidene) forms of a tungsten complex on a SBA15 silica surface. Such equilibrium is possible through the coordination of W to the surface‐adjacent [(≡Si−OH) (≡Si−NH2 )] groups, which behave as a [N, O] pincer ligand. W=W(≡C t Bu)(CH2 t Bu)3 .